The First World War - Cawood, Ian (Routledge, 2001)
Examines the outbreak, events themselves and the aftermath of the Great War, and the political, social and economic effects on the European countries involved.
Keywords: World War, 1914-1918.; Guerre mondiale, 1914-1918.; HISTORY -- Military -- World War I.; 1914-1918